ORGANIZATION OF PSYCHOSOMATIC CARE FOR PATIENTS WITH CARDIAC PATHOLOGY - V. S. Skripov; A. D. Gubernskova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. The prevalence of mental disorders, especially anxious and depressive calculi, among cardiac patients is significant. There is no doubt that it affects the cardiovascular system. The objective of the study was to analyze the prevalence of anxiety and depressive disorders among patients with cardiac pathology in the large hospital; and also to assess the provision of patients with this pathology with psychosomatic beds. Material and methods. In the course of the study, a questionnaire was conducted among 264 patients in the large cardiology department in St. Petersburg. The respondents were asked general and specialized (HADS questionnaire – screening for anxiety and / or depression) questions. With the help of special formulas on the basis of the received data, the required number of psychosomatic beds and regular positions of psychotherapists for the treatment of psychosomatic pathology for the city of St. Petersburg was calculated. Results. The findings confirmed the presence of a significant proportion of anxiety and / or depressive disorders among patients with diseases of the circulatory system. In addition to objective data, a significant percentage of interviewed patients associate the development of the underlying disease with emotional stress. Special attention is required by the age group of 60–75 years and older; men and women equally. It is important to note that the specific weight of clinically expressed forms is significant. This group of patients needs psychotherapeutic treatment in addition to the therapy of cardiac disease, which the respondents admit. Conclusions. Despite such a significant relevance, the organization of medical care for these patients in St. Petersburg is not enough. The perspectives of solving the problem were determined: an increase of stuff psychotherapists in multidisciplinary hospitals, integration of psychotherapeutic care into the outpatient stage of treatment.